Evidence to guide the optimal timing for pre‐chemotherapy blood tests for early breast, colorectal cancer and diffuse large B‐cell lymphoma - Pinkie Chambers (Wiley, 2021)
Abstract Background Re‐designing services and processes to meet growing demands in chemotherapy services is necessary with increasing treatments. There is little evidence guiding the timing and thresholds to be attained of pre‐chemotherapy blood assessments, namely neutrophils. Methods A survey was developed and distributed to health professionals in the United Kingdom (UK) to examine current practice in timing and threshold values of neutrophils and platelets before treatment administration. This was followed by a retrospective cohort study, using data from electronic patient record systems; including patients initiating treatment between January 2013 and December 2018, to determine a safe timeframe for blood assessments; comparing neutrophil, platelet, creatinine and bilirubin levels at different time points. Results The survey captured 25% of hospitals in the UK and variations were apparent in both the timing of assessments and thresholds needed, particularly for neutrophils. 616 (6.5%) of 4007 patients included had neutrophil levels measured twice within 7 days of treatment (with the first level taken beyond 3 days and the second test being within 3 days of treatment‐ the UK standard). Of the patients that attained an acceptable neutrophil level at their first test, five of the 616 (0.8%) became ineligible for administration from the test 2 level. 23% of patients improved their grade and became eligible for treatment. Little difference was observed for platelets. Conclusions We have demonstrated that extending the timeframe for blood tests can be safe, however, this practice may cause unnecessary delays for patients if only an early test is relied on for eligibility.